Rheological behavior of denatured whey crosslinked by transglutaminase on different quantities and reaction time (Research, Society and Development, 2021)
This study aimed to evaluate the rheological behavior of catalyzing the reaction of denatured whey (WPD) with the microbial transglutaminase (TG) as a function of reaction time and amount of TG. The rheological study was performed according to concentrations of 8, 14, 18, 22, and 26 U / g enzyme microbial transglutaminase and reaction times of 8, 16 and 24 hours, in which the model of Ostwald-de-Waelle ( Power law) was used to adjust the experimental data. The model showed excellent adjustment with determination coefficient values (R²) greater than 0.99. It was observed that the addition of TG provided a decrease in viscosity and increased shear rates. The increase in shear stresses was also observed and the solutions presented flow behavior indices (ⴄp) less than 1, indicating that the solutions of WPD + TG present behavior of non-Newtonian fluids of the pseudoplastic type. It was also found that the reaction times have influence on the increase in behavior index and viscosity of the solution. According to the results found, it is possible to affirm that the reaction times and the amounts of TG are decisive in the processes of obtaining quality films and gels, which can yield better products after the optimization of these factors.